CAUSE AND OCCURRENCE OF Ascaridia galli (SCHRANK, 1788) FREEBORN, 1923 IN CHICKEN EGGS - V. F. NIKITIN; I. PAVLASEK (Российский паразитологический журнал, 2016)
Analysis of the generalized literature reports and the own case of detection Ascaridia galli in chicken eggs is provided. Data on migration and unusual localization of these nematodes and larvae of species of the suborder Ascaridata are being discussed (Skryabin, 1915). The results allow us to presume that the incorrect localization of parasites is not casuistry but a component of parasites' evolution, their survival and expansion of their habitat. Description of morphology A. galli detected in a bird's egg is submitted. Figures of separate body parts and organs A. galli are presented. The unusual localization of helminths is a result of changing physical and biochemical conditions of their habitat and biological competition with other inhabitants including own species at high intensity of infection. Measures of protection against ascariasis and its therapy are necessary to prevent ascarids (roundworms) in birds' eggs. The prevention measures consist in avoiding infection of birds. The results of coproovoscopy shown that birds’ dehelmintization contributes to their migration.